Revitalising Maskan during ʿIddah: A Fiqh Analysis of Contemporary Post-Divorce Challenges in Indonesia - Muhamad Hasan Sebyar; Anisa Anisa; Hadi Asrori; Sukiati Sukiati; Moh. Buny Andaru Bahy (Faculty of Sharia, UIN Jurai Siwo Lampung, 2026)
This article explores the role of maskan (post-divorce residential rights) during the ʿiddah period as a meaningful mechanism for post-divorce reconciliation, employing a normative–empirical research design. The study integrates a conceptual analysis of Islamic legal sources with a socio-legal approach that engages contemporary legal practices, mediation processes, and the practical implementation of family law in Indonesia. Rather than treating maskan as an abstract doctrinal provision, this research situates it within the lived experiences of divorcing couples and legal actors. The findings reveal that when maskan is reduced to a mere legal formality, its capacity to foster dialogue, emotional stabilisation, and reconciliation is substantially weakened. In such contexts, residential arrangements during ʿiddah often fail to provide the psychological and relational space necessary for reflection and communication between former spouses. Conversely, empirical evidence shows that residential continuity during the ʿiddah period—when accompanied by effective mediation mechanisms and clear legal safeguards—can help prevent conflict escalation and significantly increase the prospects for marital reconciliation. By engaging contemporary socio-legal realities, this study reframes maskan as a protective and relational institution rather than a static legal rule. Drawing on the objectives of Islamic law (maqāṣid al-sharīʿah), maskan is conceptualised as serving broader aims, including the preservation of family integrity, the protection of human dignity, and the maintenance of social stability. On this basis, the article proposes a contextualised framework that bridges normative Islamic principles with practical legal needs. Policy recommendations include developing community-based transitional housing schemes, institutionalising court-integrated mediation during the ʿiddah period, and enforcing legal protections against unlawful eviction. Reconceptualised in this way, maskan emerges as both a legal entitlement and a socio-institutional instrument, enabling the ʿiddah period to function as a constructive phase that balances women’s rights, legal certainty, and the realistic possibility of post-divorce reconciliation. The primary academic contribution of this article lies in its reconceptualisation of maskan as a relational socio-legal institution within Islamic family law. By integrating normative Islamic legal principles with empirical socio-legal insights, this study moves beyond doctrinal readings that frame maskan solely as a post-divorce obligation.